2021
DOI: 10.1111/febs.16170
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic code during mycobacterial infections: therapeutic implications for tuberculosis

Abstract: Epigenetics involves changing the gene function without any change in the sequence of the genes. In the case of tuberculosis (TB) infections, the bacilli, Mycobacterium tuberculosis (M.tb) uses epigenetics as a tool to protect itself from the host immune system. TB is a deadly disease-causing maximum death per year due to a single infectious agent. In the case of TB, there is an urgent need for novel host-directed therapies which can effectively target the survival and long term persistence of the bacteria wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 132 publications
(227 reference statements)
0
11
0
Order By: Relevance
“…Fatima et al. [19] provide a broad overview of the different epigenetic modifications and discuss their reversibility in order to improve current host‐directed therapies against tuberculosis.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…Fatima et al. [19] provide a broad overview of the different epigenetic modifications and discuss their reversibility in order to improve current host‐directed therapies against tuberculosis.…”
Section: Figmentioning
confidence: 99%
“…Mtb is also using epigenetic modifications to evade host immunity, and recent studies have shown that in turn, Mtb infections affect the host epigenome to favour pathogenic survival. Fatima et al [19] provide a broad overview of the different epigenetic modifications and discuss their reversibility in order to improve current host-directed therapies against tuberculosis.…”
mentioning
confidence: 99%
“…Epigenetic markers that confer specific phenotypes have a great potential as biomarkers for the diagnosis and progression of diseases ( Figure 2 ; Batista et al, 2020 ; Fatima et al, 2021 ). Moreover, epigenetic regulation is also a quick response to changes in the environment and may be reversible.…”
Section: Introductionmentioning
confidence: 99%
“…miRNAs are involved in the epigenetic mechanisms of regulation of cell development, proliferation, differentiation, apoptosis and even anti-inflammatory and pro-inflammatory stimuli. MiRNAs promote a dual role in M. tuberculosis infection, persistence, and host immune system modulation ( Batista et al, 2020 ; Fatima et al, 2021 ). These molecules have great potential as biomarkers for diagnosis of disease and its progression to disease.…”
Section: Introductionmentioning
confidence: 99%
“…Over the past decade, epigenetic mechanisms have become increasingly important in our understanding of pathogenicity, host immunity, hypoxic survival, and virulence. Epigenetics can affect gene expression without altering the DNA sequence, not only in eukaryotes but also in bacteria, in which DNA methylation is one of the main epigenetic mechanisms for the regulation of gene expression ( Fatima et al., 2021 ). Studies on the correlation between DNA methylation and mechanisms of drug resistance in Mtb have recently attracted extensive attention.…”
Section: Introductionmentioning
confidence: 99%